Tanẓīm al-Taqālid al-‘Ilmīyah Islāmīyah fī Jāwah fī al-Qarn al-Tāsi‘ ‘Ashar wa Nufūḍuh Naḥw al-Taṭawwur al-Islāmī fī Indūnīsīyā - Nurhakim Nurhakim (Studia Islamika, 1995)
Special study of the development of scientific tradition of Islam in Java in the 19th century has not been done yet this area is the center of religious institutions and traditional Islamic education. If in the early centuries of Islamic science centers has given rise to a number of 'scholars' and major works are in Pasai, Malacca then Aceh, the 19th century it has been shifted to the center of Java.This paper intends to describe about the formation, development and influence of the Islamic intellectual tradition that includes institutional elements such as mosques, actors such as students-chaplain, system, method, process of transmitting knowledge, books and software facilities used in the 19th century.DOI: 10.15408/sdi.v2i4.822